2012
DOI: 10.1177/2151458512444288
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Fracture Center

Abstract: Objective: Since April 1, 2008, patients aged 65 years presenting with a hip fracture at Ziekenhuisgroep Twente, Almelo (ZGT-A), The Netherlands, have been admitted to the geriatric fracture center (GFC) and treated according to the multidisciplinary treatment approach. The objective of this study was to evaluate how implementation of the treatment approach has influenced the quality of care given to older patients with hip fracture. Design: Prospective cohort study with historical control group. The use of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 29 publications
2
45
1
Order By: Relevance
“…24 A study in the Netherlands showed that a geriatrician-led multidisciplinary approach was a key feature in reducing complications and 30-day readmission rates. 25…”
Section: Comparison With the Existing Literaturementioning
confidence: 99%
“…24 A study in the Netherlands showed that a geriatrician-led multidisciplinary approach was a key feature in reducing complications and 30-day readmission rates. 25…”
Section: Comparison With the Existing Literaturementioning
confidence: 99%
“…This has also been shown to lead to improved clinical outcomes [1012]. Studies measuring the effects of guidelines on quality of care have shown significant improvements in the process of care [1316].…”
Section: Introductionmentioning
confidence: 99%
“…However, we found no differences in readmission rates when comparing orthogeriatric care to traditional care. The literature seems to reveal inconsistency in the study of readmission rates; two prospective observational studies with retrospective (historical) control cohorts found decreases in such rates [4,5], while several studies found no differences [6,9,31,32]; the time lapse before assessing readmission rates varied from 30 days [5,6,32] to 12 months [31]. Valid comparison of readmission rates was also hindered by variation as to the data sources.…”
Section: Discussionmentioning
confidence: 99%
“…No similar association was reported in earlier studies investigating both postoperative complications and readmissions. Some studies report a decrease in postoperative complications comparing traditional care to orthogeriatric care, yet no difference in readmission rates were found [6,9]; other studies [4,5] found a significant decrease in both postoperative complications and readmissions. Thus, the overall changes in postoperative complications are not consistently associated with variations in readmission rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation